Quantized growth of semiconductor nanoparticles, investigation of aggregation dynamics and the growth kinetics - Dagtepe, Pinar (Kansas State University, 2010)
Colloidal semiconductor nanoparticles will be important and practical next generation materials that can be cheaply manufactured. The objective of this project is to gain more inside into chemistry is used to control the formation and assembly of semiconductor nanoparticles (NPs). As a model system CdSe and CdTe nanoparticles are used in this work. The growth kinetics, aggregation dynamics, and heterogeneous growth of NPs by using novel tools such as; in-situ monitored fluorescence and absorption techniques, time-resolved and static fluorescence spectroscopy, TEM (transmission electron microscopy), and numerical simulations are studied. This study can be divided into the following four parts. The first part presents experimental observation of the quantized growth of CdTe quantum dots (QD). The high-temperature absorption spectra indicate the evolution of multiple peaks corresponding to various sizes of QDs. The observed aggregation is driven by dipole-dipole interaction of NPs. The second part is an investigation of the aggregation dynamics of magic-sized CdTe quantum dots and how this process can be controlled. It is shown that the growth kinetics of the QDs is very sensitive to the Cd/Te ratio. Cd-rich conditions form very different aggregation pattern due to the lack of formation of magic-sized nanoparticles. Simulations also suggest that the formation mechanism is mainly coalescence of the particles rather than the ‘neck formation’ within the CdTe aggregates. The next part investigates the growth of NPs in the presence of two distinctly sized NPs in the bimodal growth regime via numerical simulations. The bimodal distribution (or quantized Ostwald ripening) technique is found to be a slower process than the repeated injection technique to focus the size distribution of NPs. Slower growth will reduce inhomogeneity in a scaled-up production of NPs. The last part focuses on the effect of addition of doping on vii heterogeneous growth and the growth kinetics. The low temperature synthesis lacks the heterogeneous growth regime. However, as the temperature is increased to 120 0C, two different sizes emerge. Addition of In dopants seems to accelerate the growth kinetics and the magic sized NPs in the solution possess a negative anisotropy that is most likely due to supperlatice formation of magic-sized NPs.
Keywords: CdTe Nanoparticles; Growth kinetics; Chemistry, Physical (0494)